Pendampingan Media Pembelajaran Berbasis Artificial Intelligence Untuk Meningkatkan Kinerja Guru - Subarkah, Pungkas; Arsi, Primandani; Rofiqoh, Dayana; Anggraeni, Ratih; Riyanto (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
One institution that plays a role in education is the school. Their contribution to the development of high-quality human resources for a country's advancement is very important, namely, educators or teachers. Therefore, the position of learning is very important to continue to be the driving force for learning units or schools so that they can continue to improve the quality of learning or the quality of learning for their students. One way to improve the quality of educators or teachers is by improving teacher performance. The purpose of this service is to improve teacher performance through artificial intelligence training, in order to add to and improve teacher performance in the current era at SMA Negeri 1 Banyumas. The methods used to carry out this activity included the preparation stage, the implementation stage, and the evaluation stage. The results obtained from the mentoring of learning media based on artificial intelligence showed that the 31 participating teachers experienced an increase in their knowledge and skills, as evidenced by the post-test results, which scored 91%. It is hoped that similar training will continue to be carried out in the future.